Tomatidine, a novel antiviral compound towards dengue virus (2019)
ABSTRACT: Dengue is the most common arboviral disease worldwide with 96 million symptomatic cases annually. Despite its major impact on global human health and huge economic burden there is no antiviral drug available to treat the disease. The first tetravalent dengue virus vaccine was licensed in 2015 for individuals aged 9 to 45, however, most cases are reported in infants and young children. This, together with the limited efficacy of the vaccine to dengue virus (DENV) serotype 2, stresses the need to continue the search for compounds with antiviral activity to DENV. In this report, we describe tomatidine as a novel compound with potent antiviral properties towards all DENV serotypes and the related Zika virus. The strongest effect was observed for DENV-2 with an EC50 and EC90 value of 0.82 and 1.61 μM, respectively, following infection of Huh7 cells at multiplicity of infection of 1. The selectivity index is 97.7. Time-of-drug-addition experiments revealed that tomatidine inhibits virus particle production when added pre, during and up to 12 h post-infection. Subsequent experiments show that tomatidine predominantly acts at a step after virus-cell binding and membrane fusion but prior to the secretion of progeny virions. Tomatidine was found to control the expression of the cellular protein activating transcription factor 4 (ATF4), yet, this protein is not solely responsible for the observed antiviral effect. Here, we propose tomatidine as a candidate for the treatment of dengue given its potent antiviral activity.